2017
DOI: 10.1242/jcs.204537
|View full text |Cite
|
Sign up to set email alerts
|

Control of mitochondrial homeostasis by endocytic regulatory proteins

Abstract: Mitochondria play essential roles in cellular energy processes, including ATP production, control of reactive oxygen species (ROS) and apoptosis. While mitochondrial function is regulated by the dynamics of fusion and fission, mitochondrial homeostasis remains incompletely understood. Recent studies implicate dynamin-2 and dynamin-related protein-1 (Drp1, also known as DNM1L), as GTPases involved in mitochondrial fission. Here, we identify the ATPase and endocytic protein EHD1 as a novel regulator of mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 43 publications
0
47
0
Order By: Relevance
“…For example, several VPS26A mutations have been implicated in atypical PD . Moreover, a recent study has demonstrated that extended/accessory members of the retromer complex, including the Eps15 homology domain protein 1 (EHD1), and its interaction partner, Rabankyrin‐5, also influence mitochondrial homeostasis . EHD1, an ATPase with homology to the dynamin family of GTPases, has a well‐established role in regulating recycling from the endocytic recycling compartment to the plasma membrane, and probably functions in the fission of tubules and vesicles from endosomes .…”
Section: Expanding the Regulation Of Mitochondrial Fusion And Fissionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, several VPS26A mutations have been implicated in atypical PD . Moreover, a recent study has demonstrated that extended/accessory members of the retromer complex, including the Eps15 homology domain protein 1 (EHD1), and its interaction partner, Rabankyrin‐5, also influence mitochondrial homeostasis . EHD1, an ATPase with homology to the dynamin family of GTPases, has a well‐established role in regulating recycling from the endocytic recycling compartment to the plasma membrane, and probably functions in the fission of tubules and vesicles from endosomes .…”
Section: Expanding the Regulation Of Mitochondrial Fusion And Fissionmentioning
confidence: 99%
“…As predicted, both EHD1 and Rabankyrin‐5 affect mitochondrial homeostasis and dynamics . Upon either EHD1‐ or Rabankyrin‐5‐depletion, mitochondria become highly static and elongated in nature, reminiscent of Drp1‐depletion.…”
Section: Expanding the Regulation Of Mitochondrial Fusion And Fissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The processes of fission and fusion are regulated by members of the GTPase Dynamin family. Fission is triggered through Drp1 and fusion through Mfn1/2 (outer mitochondrial membrane fusion) and OPA1 (inner mitochondrial membrane fusion) . Both fission and fusion proteins are regulated through proteolysis and post‐translational modifications .…”
Section: Mitochondrial Dynamicsmentioning
confidence: 99%
“…Drp1 originates from nuclear DNA and following translation, remains cytosolic , undergoing post‐translational modification, including phosphorylation prior to recruitment to the mitochondria . Although contact with the endoplasmic reticulum is believed to designate the fission point on the mitochondrion , Drp1 is essential for the fission process, inducing fission via its GTPase activity following self‐assembly .…”
Section: Mitochondrial Dynamicsmentioning
confidence: 99%